Naturalization of whiteness and associated privileges in university spaces marked by affirmative policies - Ortiz Piedrahita, Vanessa (2022)
The article describes and interprets the main ideas that white university students from Colombia and Brazil develop about whiteness. Based on their speeches and narratives, we discuss the naturalization of whiteness in ethnic and racial terms from the perspective of social sciences. We also expose some reflective narratives about the meaning of whiteness and as a position of priviledge and power in educational contexts marked by policies of affirmative action. This investigation contextualizes the importance of the study of whiteness for the understanding of raciaized relations in Latin America and presents some considerations that confirm that, despite the invisibility of whiteness as a hegemonic ideology, it has practical and symbolic effects, even in contexts marked by miscegenation and racial democracy.